Pre-Service EFL Teachers’ Perception of Using Podcast as a Learning Media to Improve Listening Skills - Mawar Estepani Hasibuan; Hendrikus Male (Journal of English Teaching, 2022)
The podcast is one of the popular tools of technology that can be used to support English language learning, especially in listening skills. Students can access podcasts everywhere and anytime to train their listening skills. Therefore, this study was employed to investigate the pre-service EFL teachers' perception of using podcasts as a learning medium in improving listening skills. The study was conducted on students of the English Language Education Department of Universitas Kristen Indonesia in May 2021. The respondents of this study were 50 students in the 2017-2019 batches. This study collected the quantitative data by distributing a questionnaire that consisted of 30 items. The data obtained were analyzed by using descriptive statistics. The result of this study showed that students hold a positive perception of using Podcasts as a learning medium in improving listening skills. Therefore, podcasts can motivate the students to become better listeners, and more confident when listening to the native speaker in the Podcast. The findings also indicated that it is essential for teachers to use appropriate instruction to achieve the best results. This media will assist both the teacher and the students in the learning process.